Evaluation of self-emulsified DIM-14 in dogs for oral bioavailability and in Nu/nu mice bearing stem cell lung tumor models for anticancer activity - Patel, Apurva R. (J Control Release, 2015)
3, 3-Diindolylmethane-14 (DIM-14), a novel lipophilic derivative of DIM, has demonstrated anticancer activity in different types of cancers. However, poor solubility and low oral bioavailability of DIM-14 limit its translational benefits in vivo. This study was carried out to improve the oral bioavailability of DIM-14 via self-emulsifying drug (SED) delivery system in dogs and to evaluate pharmacodynamic characteristics of SED against H1650 stem cell tumor models. DIM-14 was incorporated into an oil, surfactant, and co-surfactant mixture using labrafil and tween-80 to obtain SED. SED were characterized by droplet size, polydispersitiy index (PDI), zeta potential, entrapment efficiency (EE), in vitro permeability and drug release (investigated with Caco-2 monolayers and dissolution apparatus respectively). Pharmacokinetic parameters in dogs were evaluated and analyzed using Winonlin. Anti-tumor activity was carried out in H1650 lung tumor model. Particle size of SED was between 230 and 246 nm and surface charge was negative and ranged from 26.50 to 28.69 mV. Entrapment efficiency of SED was 85%. Pharmacokinetic evaluation in dogs showed increased Cmax (39.18 ± 7.34 vs 21.68 ± 6.3 µg·dL-1), higher AUC0–t (34,481.34 ± 1125.46 vs 14,159.53 ± 702.20 µg·min·dL-1) and improved absorption with 3 times more bioavailability of SED compared to DIM-14 solution. SED showed ~30–59% tumor volume/weight reduction in H1650 tumor model compared to DIM-P solution. Our studies demonstrate the potential application of self-emulsifying drug delivery system (SEDDS), that enhances oral absorption of DIM-14 and increased anti-tumor activity against lung tumor models.